2010
DOI: 10.1080/1745039x.2010.486603
|View full text |Cite
|
Sign up to set email alerts
|

A model to optimise the requirements of lactating dairy cows for physically effective neutral detergent fibre

Abstract: This study modelled multiple physiological responses of dairy cows to physical and chemical characteristics of a diet aiming to optimise their requirements for physically effective neutral detergent fibre, expressed inclusive of particles-dry matter > 8 mm (peNDF > 8). Extensive research data, comprising a wide range of feeding conditions (n = 64 studies and 257 different dietary treatments), were used to parameterise the model, while statistical modelling was used to account for the inter- and intra-experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 15 publications
4
42
0
Order By: Relevance
“…According to the results of the present study, it is suggested that Zebeli's rules are probably valid for the TMRs commonly used in the United States and Europe to feed lactating cows (500 g/kg forage and 500 g/kg concentrates, Zebeli et al, 2010), but the opposite trend might be present in concentrated TMR containing only 300 g/kg DM roughage with peNDF below 104 g/kg DM, as used in this study to feed nonlactating cows.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…According to the results of the present study, it is suggested that Zebeli's rules are probably valid for the TMRs commonly used in the United States and Europe to feed lactating cows (500 g/kg forage and 500 g/kg concentrates, Zebeli et al, 2010), but the opposite trend might be present in concentrated TMR containing only 300 g/kg DM roughage with peNDF below 104 g/kg DM, as used in this study to feed nonlactating cows.…”
mentioning
confidence: 81%
“…According to the literature, ruminal pH should not be <5.8 for >5 to 6 h/day, to minimize health disturbances due to SARA (Zebeli et al, 2012). A model based on 64 studies and 257 different dietary treatments found that content of NDF above the 8 mm sieve (physically effective NDF, peNDF) >18.5% of dietary DM prevents SARA (Zebeli et al, 2010 and. SARA may result from insufficient peNDF in dairy cow rations that reduces rumination and buffer secretion via saliva to the rumen to maintain pH, especially under massive volatile fatty acid (VFA) accumulation (Plaizier et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the limited dry matter (DM) forage intake capacity of cattle (Allen 2000;Zebeli et al 2010a), which would result in a limited energy and nutrient intake in lactating dairy cows, hence not reaching the requirements for high milk yields. Therefore, developing forage-based feeding strategies requires a better understanding on the effects of forages on digestive processes such as particle size kinetics, dynamics of particle change through the gastrointestinal tract (GIT) and turnover of nutrients including the water within the GIT, all of which have strong effects on ruminal degradation and regulation of the passage rate and feed intake capacity of cattle (Kennedy 2006;Zebeli et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrate contains high levels of rumen fermentable carbohydrates (RFC). Excess concentrate supplementation will decrease the rumen pH value, increase the risk of subclinical ruminal acidosis (SARA), and lower the rumen degradation rate of dietary fiber and feed conversion efficiency [5] (Zebeli et al 2010). The adverse effects of fat supplementation on rumen fermentation can be prevented with rumen inert fats, such as fatty acid calcium salts and saturated fat [6] (Bernard and Kertz 2009).…”
mentioning
confidence: 99%